Robert's uterus-rare cause of intractable dysmenorrhea and chronic pelvic pain - Aruna Nigam; Namoijam Basanti; Sumedha Sharma; Neha Gupta; Abhinav Jain (Wolters Kluwer Medknow Publications, 2021)
Robert's uterus is a rare type of congenital uterine anomaly where septum divides the uterine cavity asymmetrically resulting in the formation of a noncommunicating hemiuterus. Patients may present with recurrent pain, dysmenorrhea, recurrent abortions, and infertility. They are often misdiagnosed as unicornuate uterus with a noncommunicating horn. Thirty-year nulliparous female with history of severe dysmenorrhea since her menarche for which she had been operated thrice with no relief, presented with severe abdominal pain. Magnetic resonance imaging findings were suggestive of possibility of accessory horn with left hematosalpinx and hemorrhagic fluid in pelvis. Intraoperatively, it was found to be thick uterine septum completely dividing the uterine cavity asymmetrically with no communication with cervix indicative of Robert's uterus.